The Influence of Current Ratio and Debt to Asset Ratio on Return on Assets at PT Adhi Karya TBK for the 2010-2022 Period - Hidayat, Ahmad Ridwan (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2024)
This research aims to analyze and determine the influence of the Current Ratio and Debt to debt-to-asset ratio on the Return on Assets at PT Adhi Karya Tbk during the 2010-2022 period. The research method used is descriptive with a quantitative approach. The data used in this research is secondary data obtained from the annual financial report of PT Adhi Karya Tbk which is listed on the Indonesia Stock Exchange. Data analysis was carried out using the SPSS 25. This research concludes that the Current Ratio significantly influences the Return on Assets, while the Debt to debt-to-asset ratio does not have a partially significant influence on the Return on Assets at PT Adhi Karya TBK. However, simultaneously, these two independent variables have a substantial effect on Return on Assets. So these findings provide important insights for the management of PT Adhi Karya TBK in managing liquidity and debt structure to increase company profitability.